The Experience of Patient Alcohol Addictions in Cognitive Behavior Therapy - Arif Dwi Cahyono (International Conference on Psychology and Education (ICPE), 2023)
Cognitive Behavior Therapy (CBT) was behavior modification techniques and changing maladaptive beliefs. This study aims to obtain a comprehensive picture of the application of Cognitive Behavior Therapy in helping individuals overcome alcohol addiction. This study uses a study case qualitative research method. The study patient was an alcoholic during 23 year. Data collection was done by triangulation method, namely in-depth interviews (depth interviews) face to face with observations and interview. The research procedure was carried out in three stages, namely the research preparation stage, the research implementation stage, and finally the research result evaluation stage. The results of the study showed that the application of Cognitive Behavior Therapy to individuals who experienced alcohol addiction showed significant changes in patient cognition, emotion and behavior. Through cognitive restructuring techniques, patient distorted cognitions become more rational. Patient were able to manage a good lifestyle, were independent in their work, respect the people around them. Changes in cognition in patient led to reduced alcohol consumption behavior.